Implementation of the Opensid Website-Based Village Information System at the Belega Village Office, Blahbatuh District, Gianyar Regency - Budiyasa, I Gede Putra; Wirata, Gede; Sulandari, Sri (Pengurus Pusat Perkumpulan Ilmuwan Administrasi Negara Indonesia (PIANI), 2025)
Abstract This study aims to examine the implementation of the village information system based on the OpenSID website at the Belega Village Office, Blahbatuh District, Gianyar Regency. The research focuses on how the policy implementation process, coordination, and obstacles faced by village officials in operating the system. This study employed a descriptive qualitative approach with data collected through observation, interviews, and literature study. The data were analyzed through the stages of collection, reduction, presentation, and verification using qualitative analysis techniques. The results show that the implementation of OpenSID in Belega Village has contributed to improving the quality of public services, particularly in terms of information transparency, accessibility of administrative services, and effectiveness of service delivery to the community. Nevertheless, several challenges remain, such as limited human resources, inadequate facilities and infrastructure, and uneven public understanding of the use of information technology. Overall, the application of OpenSID in Belega Village has been running fairly well, although it still requires capacity building for village officials and stronger infrastructure support to ensure that its benefits can be more optimally realized. Keywords: Implementation, Village information system, Public service, OpenSID, Administration